Design, synthesis, in silico studies and in vitro evaluation of isatin-pyridine oximes hybrids as novel acetylcholinesterase reactivators. (1st January 2021) - Kitagawa, Daniel A. S.; Rodrigues, Rafael B.; Silva, Thiago N.; dos Santos, Wellington V.; da Rocha, Vinicius C. V.; de Almeida, Joyce S. F. D.; Bernardo, Leandro B.; Carvalho-Silva, Taynara; Ferreira, Cintia N.; da Silva, Angelo A. T.; Simas, Alessandro B. C.; Nepovimova, Eugenie; et al.
Abstract: Organophosphorus poisoning caused by some pesticides and nerve agents is a life-threating condition that must be swiftly addressed to avoid casualties. Despite the availability of medical countermeasures, the clinically available compounds lack a broad spectrum, are not effective towards all organophosphorus toxins, and have poor pharmacokinetics properties to allow them crossing the blood-brain barrier, hampering cholinesterase reactivation at the central nervous system. In this work, we designed and synthesised novel isatin derivatives, linked to a pyridinium 4-oxime moiety by an alkyl chain with improved calculated properties, and tested their reactivation potency against paraoxon- and NEMP-inhibited acetylcholinesterase in comparison to the standard antidote pralidoxime. Our results showed that these compounds displayed comparable in vitro reactivation also pointed by the in silico studies, suggesting that they are promising compounds to tackle organophosphorus poisoning.